PENGARUH PENGENDALIAN INTERNAL, KESESUAIAN KOMPENSASI, KETAATAN ATURAN AKUNTANSI, DAN PERILAKU TIDAK ETIS TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI (Studi Empiris Pada SKPD Kabupaten Bengkalis) - Dewi, Chindy Kurnia Rahma; Surya, Raja Adri Setiyawan; Hasan, Mudrika Alamsyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aimed to examine the influence of internal control, compansation suitability, compliance to accounting rules, and unethical behavior on tendency of accounting fraud. Populations of this research are SKPD Districk of Bengkalis. The technical sampling of this research uses total sampling. Data of this research obtained from at officer accounting and accounting staff. Type of data used are primary data. Data collection method used is survey, usingquestionnaire. Analysis used multiple linear regression. Analiysis statistical finding of statistical test provide following result : 1) internal control has effect on tendency of accounting fraud where the significant value 0,000 < 0,05 (H1 accepted), 2) compansation suitability has effect on tendency of accounting fraud where the significant value 0,017 < 0,05 (H2 accepted), 3) compliance to accounting rules has effect on tendency of accounting fraud where the significant value 0,009 < 0,05 (H3 accepted), 4) unethical behavior has effect on tendency of accounting fraud where the significant value 0,008 < 0,05 (H4 accepted). The results of the research indicates that internal control, compansation suitability, compliance to accounting rules effect significant negative on tendency of accounting fraud, while unethical behavior effect significant positif on tendency of accounting fraud.Keywords: Control, compansation, Rules, Behavior, Fraud